Are IV or oral steroids better for treatment of acute COPD exacerbation?. Issue 1 (January 2017) - Stump, Laura E.; Geurin, Michael D.
Abstract : EVIDENCE‐BASED ANSWER : Intravenous (IV) steroids are no more effective than oral steroids for the initial treatment of acute exacerbations of chronic obstructive pulmonary disease (COPD) and do not reduce risk of treatment failure, relapse, or mortality; moreover, IV steroids are associated with increased hyperglycemia (SOR: A, systematic review of RCTs). Initial treatment with oral steroids may be associated with lower costs and shorter hospital stay (SOR: B, retrospective cohort study).